PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN LAPTOP MEREK ACER DENGAN KEPERCAYAAN MEREK SEBAGAI VARIABEL MEDIASI PADA MAHASISWA KOTA TEBING TINGGI: Studi Kuantitatif pada Mahasiswa Pengguna Laptop Acer di Kota Tebing Tingg - Attila Rania Insyira Siregar; Rastiwi; Yenni Arfah; Rajagukguk, Frederik Rudy Sentosa (ITB AAS Indonesia Surakarta, 2025)
This research aims to examine the effect of product quality and brand image on purchasing decisions for Acer laptops among students in Tebing Tinggi City, with brand trust as a mediating variable. The purpose of the study was to analyze the extent to which product quality and brand image influence purchasing decisions, both directly and indirectly through brand trust. The research method used a quantitative approach with SEM (Structural Equation Modeling) analysis based on Smart PLS, involving 96 respondents selected by proportional random sampling from three universities. The results showed that brand image had a positive and significant effect on purchasing decisions (H2 accepted), while product quality had no direct effect (H1 rejected). However, product quality and brand image significantly increased brand trust (H3 and H4 accepted), which in turn had a positive effect on purchasing decisions (H5 accepted). Brand trust was also shown to act as a full mediator in the relationship between product quality and brand image with purchasing decisions (H6 and H7 accepted). These findings highlight the importance of brand image and brand trust in Acer's marketing strategy, while product quality needs to be communicated more effectively to influence purchasing decisions.